Three green financial policies to address climate risks - Francesco Lamperti; Valentina Bosetti; Andrea Roventini; Massimo Tavoni; Tania Treibich (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
Which policies can increase the resilience of the financial system to climate risks? Recent evidence on the significant impacts of climate change and natural disasters on firms, banks and other financial institutions call for a prompt policy response. In this paper, we employ a macro-financial agent- based model to study the interaction between climate change, credit and economic dynamics and test a mix of policy interventions. We first show that financial constraints exacerbate the impact of climate shocks on the economy while, at the same time, climate damages to firms make the banking sector more prone to crises. We find that credit provision can both increase firms' productivity and their financial fragility, with such a trade-off being exacerbated by the effects of climate change. We then test a set of 'green' finance policies addressing these risks, while fostering climate change mitigation: i) green Basel-type capital requirements, ii) green public guarantees to credit, and iii) carbon-risk adjustment in credit ratings. All the three policies reduce carbon emissions and the resulting climate impacts, though moderately. However, their effects on financial and real dynamics is not straightforwardly positive. Some combinations of policies fuel credit booms, exacerbating financial instability and increasing public debt. We show that the combination of all three policies leads to a virtuous cycle of (mild) emission reductions, stable financial sector and high economic growth. Additional tools would be needed to fully adapt to climate change. Hence, our results point to the need to complement financial policies cooling down climate-related risks with mitigation policies curbing emissions from real economic activities.
Keywords: C63; E5; O44; Q5; 330; Climate change; endogenous growth; financial stability; macroprudential policy; agent-based model